The precautionary principle of environmental law: an ounce of prevention is worth a pound of cure (2015)
Environmental protection is a topical issue of concern across the global community in the face of undesirable consequences of environmental degradation. Such consequences include global warming, climate change, flooding, desertification, loss of biodiversity, scarcity of water, food and intense weather conditions. Various principles have been developed in the quest for acceptable regulatory framework for the protection of the environment, including the principle of precaution. This Article adopts the view that precautionary principle is a step ahead of the preventive principle, arguing in accord with Article 15 of the Rio Declaration that environmental measures must foresee, prevent and deal with the causes of environmental degradation which threaten to cause serious or irreversible damage, notwithstanding the absence of full scientific evidence. The article adopts the doctrinal research method and divided into six parts. The introduction is followed by an overview of the precautionary principle while the third part examines the criteria for its application and in the fourth pan. the reasons for and advantages of the precautionary principle are examined. It analyses the debates and criticisms of the Precautionary Principle in the fifth part and it concludes with a summary and recommendation that precaution is to be preferred to remedial approaches.